Study of arsenic adsorption in water using nanocomposite based on magnetite nanoparticles and tara gum - Ponce Álvarez, Silvia (2025)
One of the pollutants that can be found in water bodies as a result of industrial activity is arsenic. Methods for the removal of this non-metal turn out to be inefficient and expensive. A new nanocomposite based on tara gum and magnetite nanoparticles was prepared for the removal of arsenic from water. The characterization of the nanocomposites prepared with different Fe3O4: tara gum ratios showed the presence of the magnetite phase by XRD and it was also measurement the particle size (13.74 nm) by TEM. The arsenic removal tests in water carried out with the nanocomposites with different magnetite content, pH variation and nanocomposite weight showed that the nanocomposite with 80% by weight of magnetite presented higher efficiency. The maximum values studied for arsenic concentration were 2 ppm, reaching 24.8% removal in 15 minutes of exposure using the nanocomposite with 80% magnetite nanoparticles.